Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Mercury speciation in pilot whale from Faroe Islands, 1977–2015 - Katrin S. Hoydal; Sissal V. Erenbjerg; Maria Dam (Environmental Pollution, 2024)

The impacts of digital transformation on fisheries policy and sustainability: Lessons from Timor-Leste - Alexander Tilley; Rodolfo Dam Lam; Denise Lozano Lazo; Joctan Dos Reis Lopes; Dede Freitas Da Costa; Maria De Fátima Belo; Joaquina Da Silva; Gilberto Da Cruz; Cristiano Rossignoli (Environmental Science & Policy, 2024)

European river typologies fail to capture diatom, fish, and macrophyte community composition - Jonathan F. Jupke; Sebastian Birk; Apostolos Apostolou; Jukka Aroviita; Annette Baattrup-Pedersen; Peter Baláži; Libuše Barešová; Saúl Blanco; María Borrego-Ramos; Herman van Dam; Elias Dimitriou; Christian K. Feld; et al. (Science of The Total Environment, 2023)

Study of the long-finned pilot whale (Globicephala melas) bile content - An indicator of ocean health - Daniela M. Pampanin; William Bossum Arnli; Jason T. Magnuson; Giovanna Monticelli; Maria Dam; Svein-Ole Mikalsen; Magne O. Sydnes (Marine Pollution Bulletin, 2023)

The bacterium Pseudomonas protegens antagonizes the microalga Chlamydomonas reinhardtii using a blend of toxins - Magdalena M. Rose; Daniel Scheer; Yu Hou; Vivien S. Hotter; Anna J. Komor; Prasad Aiyar; Kirstin Scherlach; Fredd Vergara; Qing Yan; Joyce E. Loper; Torsten Jakob; Nicole M. van Dam; et al. (Environmental Microbiology, 2021)
Summary The unicellular alga Chlamydomonas reinhardtii and the bacterium Pseudomonas protegens serve as a model to study the interactions between photosynthetic and heterotrophic microorganisms. P . protegens secretes the cyclic lipopeptide orfamide A that interferes with cytosolic Ca 2+ homeostasis in C . reinhardtii resulting in deflagellation of the algal cells. Here, we studied the roles of additional secondary metabolites secreted by P . protegens using individual compounds and co‐cultivation of algae with bacterial mutants. Rhizoxin S2, pyrrolnitrin, pyoluteorin, 2,4‐diacetylphloroglucinol (DAPG) and orfamide A all induce changes in cell morphology and inhibit the growth of C . reinhardtii . Rhizoxin S2 exerts the strongest growth inhibition, and its action depends on the spatial structure of the environment (agar versus liquid culture). Algal motility is unaffected by rhizoxin S2 and is most potently inhibited by orfamide A (IC 50 = 4.1 μM). Pyrrolnitrin and pyoluteorin both interfere with algal cytosolic Ca 2+ homeostasis and motility whereas high concentrations of DAPG immobilize C . reinhardtii without deflagellation or disturbance of Ca 2+ homeostasis. Co‐cultivation with a regulatory mutant of bacterial secondary metabolism (Δ gacA ) promotes algal growth under spatially structured conditions. Our results reveal how a single soil bacterium uses an arsenal of secreted antialgal compounds with complementary and partially overlapping activities.

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Legacy Pollutants are Declining in Great Skuas (Stercorarius skua) but Remain Higher in Faroe Islands than in Scotland - Sjurdur Hammer; Ruedi G. Nager; Sarah Alonso; Rona A. R. McGill; Robert W. Furness; Maria Dam (Bulletin of Environmental Contamination and Toxicology, 2016)

Perfluoroalkyl substances (PFASs) in food and water from Faroe Islands - Ulrika Eriksson; Anna Kärrman; Anna Rotander; Bjørg Mikkelsen; Maria Dam (Environmental Science and Pollution Research, 2013)

Are cadmium, lead and mercury concentrations in mosses across Europe primarily determined by atmospheric deposition of these metals? - Winfried Schröder; Marcel Holy; Roland Pesch; Harry Harmens; Ilia Ilyin; Eiliv Steinnes; Renate Alber; Yuliya Aleksiayenak; Oleg Blum; Mahmut Coşkun; Maria Dam; Ludwig De Temmerman; et al. (Journal of Soils and Sediments, 2010)

First thorough identification of factors associated with Cd, Hg and Pb concentrations in mosses sampled in the European Surveys 1990, 1995, 2000 and 2005 - Marcel Holy; Roland Pesch; Winfried Schröder; Harry Harmens; Ilia Ilyin; Renate Alber; Yuliya Aleksiayenak; Oleg Blum; Mahmut Coşkun; Maria Dam; Ludwig De Temmerman; Natalia Fedorets; et al. (Journal of Atmospheric Chemistry, 2009)

A comparison of national approaches to setting ecological status boundaries in phytobenthos assessment for the European Water Framework Directive: results of an intercalibration exercise - Martyn Kelly; Cathy Bennett; Michel Coste; Cristina Delgado; François Delmas; Luc Denys; Luc Ector; Claude Fauville; Martial Ferréol; Malgorzata Golub; Amelie Jarlman; Maria Kahlert; et al. (Hydrobiologia, 2009)